2009
DOI: 10.1375/bech.26.3.190
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Behavioural Intervention for Overweight and Obese Adolescents Illustrated by Four Case Studies

Abstract: This article reports four case studies illustrating the implementation of the ChooseHealthProgram, a cognitive behavioural lifestyle intervention for overweight and obese adolescents. Participants were an overweight (12 years) and obese (15 years) female, and an overweight (14 years) and obese (12 years) male. The program was delivered by provisional psychologists with program specific training and supervision. All participants demonstrated improvements in body composition, and maintained or improved dietary q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…There were no studies from the Pacific Islands. We found that 5 studies concentrated on children, 8,14-17 3 on youth, 18-20 6 on adults, 21-26 and 2 on older adults. 13,27 In 3 of these studies, all the participants were female, 23,25,27 whereas in the other studies participants represented both genders.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…There were no studies from the Pacific Islands. We found that 5 studies concentrated on children, 8,14-17 3 on youth, 18-20 6 on adults, 21-26 and 2 on older adults. 13,27 In 3 of these studies, all the participants were female, 23,25,27 whereas in the other studies participants represented both genders.…”
Section: Resultsmentioning
confidence: 88%
“…Some studies that examined the impact of PA (38%) also assessed body composition. 13,17,18,21,26,27 Blood pressure was measured in 6 studies (38%). 13,20,21,23,24,26 PA was either measured directly using accelerometers 8,18 or indirectly through questionnaires.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations